PENGARUH KEDISIPLINAN DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN DI GO SUMBER PLASTIK GRESIK : Discipline, Team Work, Employees performance - Astanto, Denny (Fakultas Ekonomi Universitas Gresik, 2021)
This research was conducted in purpose to investigate and prove the influence of employee discipline and team work on GO Sumber Plastik Gresik’s employee performances. The approach used was quantitative approach using double linier regression analysis. Afterwards, the sample taken amounted 60 respondents and the data gathered by spreading questionaires. The results showed that employee discipline did not provide a positive and significant influence on GO Sumber Plastik Gresik’s employee performances. However, team works had provided positive and significant influence on GO Sumber Plastik Gresik’s employee performances. Simulataneously, discipline and team work had positive and significant influence on GO Sumber Plastik Gresik’s employees performances. Keywords